2012
DOI: 10.1007/s00330-012-2708-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting in difficult aortic arch anatomy with or without a new dedicated guiding catheter: preliminary experience

Abstract: • Complex anatomy of the aortic arch is not rare • Endovascular carotid artery stenting (CAS) is more difficult when the anatomy is complex • A new dedicated guiding catheter may help CAS when the arch anatomy is complex • The new dedicated guiding catheter may be less risky in complex arches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…10 A complex aortic arch anatomy (i.e., Type III arch and/or bovine arch) may increase the technical difficulties of CAS and the risk of neurological complications via femoral access. 1012 A study by Gray et al. 13 showed that more than 20% of stroke were related to catheterization difficulties, especially when procedures were performed by less experienced interventional physicians.…”
Section: Discussionmentioning
confidence: 99%
“…10 A complex aortic arch anatomy (i.e., Type III arch and/or bovine arch) may increase the technical difficulties of CAS and the risk of neurological complications via femoral access. 1012 A study by Gray et al. 13 showed that more than 20% of stroke were related to catheterization difficulties, especially when procedures were performed by less experienced interventional physicians.…”
Section: Discussionmentioning
confidence: 99%
“…8 Additionally, prior XRT has been shown to accelerate the formation of atherosclerotic lesions and weaken the integrity of the vessel wall, further complicating open intervention. 1,6 Alternatively, CAS avoids such surgical complications, but carries an increased risk of CVA due to atheroembolic phenomena. Recent literature, however, has demonstrated comparable outcomes for CEA and CAS following prior XRT, 3 so the treatment modality of choice in this setting is largely patient-and/or physician-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has demonstrated a higher incidence of neurological complications and technical difficulty in CAS patients with arch anomalies, specifically those with type III anatomy. [4][5][6] The steep angulation of the great vessels makes maneuvering the stent difficult and may increase the risk of distal embolization from resultant vessel damage and plaque dislodgment. 5 Although carotid stents have undergone design improvements, and EPDs are routinely used, periprocedural embolic events remain the Achilles' heel of this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reflects a single‐center experience so that the observations have the limit of stemming from a restricted number of operators with similar experience. In particular, it should be emphasized that we did not adopt dedicated carotid catheters and such catheters have been recently shown to facilitate procedure completion in the case of hostile aortic arch anatomies .…”
Section: Discussionmentioning
confidence: 99%